Democracy compromised : chiefs and the politics of the land in South Africa - Ntsebeza, Lungisile (Afrika-Studiecentrum series, 2005)
'Democracy Compromised' addresses two related questions: firstly, how, despite their role in the apartheid state, traditional authorities have not only survived but gained unprecedented powers in rural governance in South Africa's democracy; and secondly, how they derive their authority.